Bio-degradable material realization for antenna fabrication in wireless communications - Thanakorn Homsai; Chuwong Phongcharoenpanich; Wipoo Sriseubsai (My University, 2018)
The biodegradable PBS material is presented to be applied for microwave device design (antenna). The PBS is forming by using compression molding. The PBS thickness is 1 mm with the flexible characteristic. In this paper, the antenna design for the operating frequency band of 2400-2500 MHz is design using the bio-degradable material with the dielectric constant of 3.2. The prototype was fabricated. The characteristics of the proposed device were presented. The effected of the curved antenna and substrate are described in this work.
Keywords: Realization (probability); Modular Robots and Swarm Intelligence